Explosion-proof film pasted outside car window and preparation method thereof
The liquid film formation method is used to prepare a TPU film with high hardness and transparency, and a second repair layer is made on its surface, which solves the problem that the existing window explosion-proof film cannot be attached to the front-mounted glass, achieving efficient impact buffering and long-term use durability.
Patent Information
- Application Number
- CN202411992418.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-28
AI Technical Summary
The existing window explosion-proof membrane cannot effectively attach the front gear glass to the outside, resulting in the glass being easily broken when impacted by external factors, and has high durability and maintenance frequency.
The liquid film formation method is used to prepare a TPU film with high hardness, high tensile strength and high transparency as the base film, and a second repair layer is made on its surface, combined with the installation of the glue layer and the protective film to make an explosion-proof film outside the car window.
It realizes the high hardness and transparency of the explosion-proof film outside the car window, which can buffer and stress disperse when exposed to external impact, extend the service life of the glass, reduce the maintenance frequency, and avoid scratches or deformations under a long-term wipe.
Smart Images

Figure CN119709036A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of vehicle window protective films, relates to vehicle window explosion-proof films, and specifically relates to an explosion-proof film for exterior application on vehicle windows and a preparation method thereof. Background Art
[0002] When vehicles (cars, urban rails, high-speed trains, etc.) are traveling at high speeds, they are easily hit by the impact of gravel bouncing off from the outside, winter power lines, trees on both sides of the road, or icicles melting and falling from high altitudes, which can easily break the windshield of the vehicle. Traditional windshield films can only be applied inside. Although they can prevent the driver and passengers from being injured after the glass is broken, they cannot drive normally after the glass is broken, and they need to be repaired and replaced immediately, which greatly wastes the passengers' time. In addition, for vehicles such as urban rails and high-speed trains, repairs and replacements will prevent them from running normally, which has a great impact on the management and control of public transportation networks. The existing technology cannot effectively solve the above problems. For example, the invention patent CN117801717A discloses an external heat-insulating window film and its preparation method, which uses PET film, TPU film, PVC film, TPH film and TPU / PVC composite film as the base film for the explosion-proof film applied to the outside of the car window. This solution has the following technical defects and cannot be solved by current technology:
[0003] (1) PET substrate has no stretchability and poor conformability. It is difficult to adhere to the outer curved surface and is prone to warping. At the same time, due to its high hardness, generally reaching above Shore D90, the instant repair coating no longer has a buffering and repairing effect on PET. It cannot withstand the friction of the front windshield wiper and will be worn out over time due to the friction of the wiper. This is the main reason why traditional window films cannot be applied externally.
[0004] (2) For conventional TPU substrates in the industry, polycaprolactone and isocyanate grafted cross-linked particles are generally used for film casting. This type of TPU has a low hardness, normally only around Shore A90. After being made into a finished windshield film, the TPU will deform under the action of long-term wiper pressure, causing orange peel texture on the windshield film, which will cause dizziness and deformation of the driver's vision.
[0005] (3) PVC and TPH are difficult to achieve high transparency and are not suitable for window film applications. At the same time, due to their hardness, they cannot be repaired in seconds. They are not resistant to windshield wipers, aging, and yellowing. The same is true for TPU / PVC composite films.
[0006] In response to the above technical problems, there is an urgent need for a film material that can be attached to the surface of the windshield, so that the windshield can play a buffering and stress dispersion role when it is impacted by external gravel or ice cones, thereby protecting the glass from shattering, greatly improving the service life of the glass in harsh environments, and reducing the frequency of maintenance. Summary of the invention
[0007] The technical problem to be solved by the present invention is to provide an explosion-proof film for car windows with good adhesion, excellent explosion-proof effect, and resistance to long-term scratching by wipers without scratches, and a preparation method thereof, in view of the shortcomings of the existing technology.
[0008] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0009] A method for preparing an explosion-proof film for a vehicle window, comprising the following steps:
[0010] S1, dissolving a polyurethane coating liquid, an isocyanate curing agent, a metal chelate catalyst, a carboxyl remover, an ultraviolet absorber and an ultraviolet stabilizer in an organic solvent, mixing, and vacuum defoaming to obtain a pre-coating liquid;
[0011] S2, coating the pre-coating liquid obtained in step S1 on the non-silicon release film, drying and curing, compounding the non-silicon release film on the other side, rolling up, and ripening to obtain a TPU film supported by non-silicon release films on both sides;
[0012] S3, dissolving hydroxy acrylate resin and isocyanate curing agent in an organic solvent, mixing to obtain a second repair coating liquid, tearing off one of the non-silicon release films on the TPU film supported by the two non-silicon release films prepared in step S2, coating the second repair coating liquid on the TPU film with one non-silicon release film torn off, drying and curing to obtain a second repair layer, and compounding a protective film on the second repair layer;
[0013] S4, mixing the installation glue with an organic solvent to obtain an installation glue coating liquid, coating it on the release film, drying and curing to obtain an installation glue layer, tearing off the other side of the non-silicone release film on the TPU film with the second repair layer and the protective film in step S3, laminating it with the installation glue layer on the release film, and ripening it to obtain an explosion-proof film for the car window.
[0014] In the above-mentioned method for preparing explosion-proof film for vehicle windows, preferably, in step S1, the mass ratio of the polyurethane coating liquid to the isocyanate curing agent, the metal chelate catalyst, the carboxyl remover, the ultraviolet absorber, the ultraviolet stabilizer and the organic solvent is 100:1.5-2.5:1.5-2.5:1.0-2.0:0.4-0.6:0.2-0.4:8-15.
[0015] In the above-mentioned method for preparing explosion-proof film for vehicle windows, preferably, in step S1 and step S3, the isocyanate curing agent is one or both of hexamethylene diisocyanate biuret curing agent and hexamethylene diisocyanate trimer curing agent; in step S1, the metal chelate catalyst is one or more of acetylacetonate organic tin, acetylacetonate organic bismuth, acetylacetonate organic zinc and acetylacetonate organic aluminum; in step S1, the carboxyl remover is one or more of glycidyl ester, glycidyl ether, glycidyl amine and carbodiimide; in step S1, the ultraviolet absorber is one or more of benzophenone ultraviolet absorbers, benzotriazole ultraviolet absorbers and triazine ultraviolet absorbers.
[0016] In the above-mentioned method for preparing explosion-proof film for vehicle windows, preferably, in step S1, the solid content of the polyurethane coating liquid is 35wt% to 40wt%, the viscosity is 7000mpa·s to 10000mpa·s, and the number average molecular weight is 30000g / mol to 50000g / mol; based on the solid content of 100wt%, the hydroxyl value of the polyurethane coating liquid is 60mgKOH / g to 120mgKOH / g, and the acid value of the polyurethane coating liquid is 5mgKOH / g to 15mgKOH / g;
[0017] In the above-mentioned method for preparing explosion-proof film for vehicle windows, preferably, in step S1, the solid content of the polyurethane coating liquid is 37wt% to 39wt%; based on the solid content of 100wt%, the hydroxyl value of the polyurethane coating liquid is 79mgKOH / g to 88mgKOH / g, and the acid value of the polyurethane coating liquid is 10mgKOH / g to 15mgKOH / g; the polyurethane coating liquid is prepared by polycarbonate polyol and isophorone diisocyanate; in steps S1 and S3, the isocyanate curing agent is a hexamethylene diisocyanate trimer curing agent, and the solid content of the hexamethylene diisocyanate trimer curing agent is 80wt% to 90wt%; In step S1, the metal chelate catalyst is an acetylacetonate-based organotin catalyst, and the solid content of the acetylacetonate-based organotin catalyst is 2wt% to 2.5wt%; in step S1, the carboxyl remover is glycidyl ester, and the solid content of the glycidyl ester is 9wt% to 11wt%; in step S1, the ultraviolet absorber is a benzotriazole ultraviolet absorber, and the solid content of the benzotriazole ultraviolet absorber is 98wt% to 100wt%; in step S1, the ultraviolet stabilizer is a hindered amine type ultraviolet stabilizer, and the solid content of the hindered amine type ultraviolet stabilizer is 98wt% to 100wt%.
[0018] In the above-mentioned method for preparing explosion-proof film for vehicle windows, preferably, in step S3, the mass ratio of the hydroxy acrylate resin to the isocyanate curing agent and the organic solvent is 100:28-32:20-40; the solid content of the hydroxy acrylate resin is 30wt%-40wt%, and the hydroxyl value of the hydroxy acrylate resin is 190mgKOH / g-200mgKOH / g; the solid content of the isocyanate curing agent is 73wt%-77wt%.
[0019] In the above-mentioned method for preparing explosion-proof film for vehicle windows, preferably, the organic solvent in step S1 is one or more of ethyl acetate, butyl acetate, acetone, butanone, N,N-dimethylformamide, N,N-diethylformamide, N,N-dimethylacetamide and N,N-diethylacetamide.
[0020] In the above-mentioned method for preparing explosion-proof film for vehicle windows, preferably, in step S3 and step S4, the organic solvent is one or more of ethyl acetate, butyl acetate, acetone and butanone.
[0021] In the above-mentioned method for preparing explosion-proof film for vehicle windows, preferably, in step S1, the viscosity of the pre-coating liquid is 2000mpa·s to 3500mpa·s, and in step S2, the coating amount of the pre-coating liquid is 168g / m 2 ~224g / m 2 In step S3, the viscosity of the second repair coating is 10mpa·s to 100mpa·s, and the coating amount of the second repair coating is 11.2g / m 2 ~16.8g / m 2 In step S4, the viscosity of the installation glue coating liquid is 500mpa·s to 2000mpa·s, and the coating amount of the installation glue coating liquid is 16.8g / m 2 ~22.4g / m 2 .
[0022] In the above-mentioned method for preparing explosion-proof film for vehicle windows, preferably, in step S2, the coating is carried out by a precision coating machine, the running speed of the pre-coating liquid on the precision coating machine is 3m / min to 5m / min, the drying temperature is 100°C to 130°C, and the curing time is 6min to 10min; the aging temperature is 45°C to 55°C, and the aging time is 3 days to 5 days;
[0023] In the above-mentioned method for preparing explosion-proof film for vehicle windows, preferably, in step S3, the coating is carried out by a precision coating machine, the running speed of the second repair coating liquid on the precision coating machine is 10m / min to 15m / min, the drying temperature is 100°C to 110°C, and the curing time is 2min to 3min;
[0024] In the above-mentioned method for preparing explosion-proof film for vehicle windows, preferably, in step S4, the coating is carried out by a precision coater, the running speed of the installation glue coating liquid on the precision coater is 15m / min~20m / min, the drying temperature is 120℃~130℃, and the curing time is 1min~2min; the aging temperature is 45℃~55℃, and the aging time is 2 days~3 days; the installation glue adopts Bostik 951059 series.
[0025] As a general technical concept, the present invention also provides an explosion-proof film for vehicle windows prepared by the above-mentioned preparation method, comprising a protective film, a second repair layer, a TPU film, an installation adhesive layer, and a release film laminated in sequence, wherein the TPU film has a visible light transmittance of ≥88%, a Shore hardness of D40 to D50, and a tensile strength of ≥50Mpa.
[0026] For the above-mentioned explosion-proof film for vehicle windows, preferably, the thickness of the instant repair layer is 10μm to 15μm; the thickness of the TPU film is 150μm to 200μm; the thickness of the installation adhesive layer is 15μm to 20μm, and the adhesion of the installation adhesive layer to the glass is ≥1200g / 25mm.
[0027] The innovation of the present invention is:
[0028] The traditional particle casting film-forming method cannot be used to produce high-hardness TPU base films because of the high melting point of high-hardness particles, the difficulty of extrusion, and poor film-forming properties. The present invention innovatively uses a liquid film-forming method, using a polyurethane coating liquid and isocyanate for curing to improve the hardness of the TPU base film, and is not affected by the high melting point of the initial high-hardness TPU particles, the difficulty of extrusion, and the poor film appearance. The high-hardness TPU film material prepared by the present invention is used as the base film of the explosion-proof film for vehicle window exteriors. While having high hardness and not easy to deform, it also has a certain degree of flexibility and is easy to apply. A second repair coating can be applied on it, which is suitable for vehicle window exteriors, especially vehicle front windshield exteriors.
[0029] Compared with the prior art, the advantages of the present invention are:
[0030] (1) The current windshield film is not suitable for external application. Either the TPU film material used is too soft, and after being scraped by the wiper for a long time, orange peel lines will appear, causing dizziness and deformation of the driver's vision. Or the film material used is too hard, and the second repair layer cannot play an effective role on the surface of the too hard film material. The film material with a purely hardened surface will still be scratched after being scraped by the wiper for a long time. The preparation method of the present invention innovatively uses a liquid film-forming method and specific raw materials to prepare a TPU film with high hardness, high tensile strength, high transparency, and a smooth surface. This is used as the base film to prepare an explosion-proof film for external application of car windows with excellent performance. In terms of technology, the hardness of the TPU base film is improved by curing the polyurethane coating liquid with isocyanate, which is not affected by the high melting point of the initial high-hardness TPU particles, the difficulty of extrusion, and the poor film appearance. In terms of the selection of key raw materials, the polyurethane coating liquid is in liquid form, thus avoiding the defects of using high-hardness TPU particles. In addition, compared with the existing complex scheme of directly using oligomers and multiple end-capping agents for cross-linking during the coating and drying stage, the present invention uses the polyurethane in the polyurethane coating liquid as a high molecular polymer, and only two curing agents are needed for cross-linking in the subsequent coating and drying stage, which makes it easier to control the stability of the product. More importantly, the present invention uses a carboxyl remover when preparing the pre-coating liquid, which can effectively avoid the carboxyl-catalyzed hydrolysis of the ester group on the main chain under high temperature and high humidity conditions, making the explosion-proof film on the car window more prone to aging, and the tensile strength drops rapidly, affecting the service life, and it cannot be torn off from the glass, affecting the later maintenance and replacement.
[0031] (2) The TPU base film produced by the preparation method of the present invention can have a Shore hardness of D40 to D50 and a tensile strength of ≥50Mpa. Due to its high hardness, the windshield explosion-proof film prepared as the base film will not deform the film material and the installation glue under the continuous scraping of the windshield wiper, avoiding obvious orange peel, and further avoiding dizziness and deformation of the driver's vision, which affects driving. It is worth noting that the harder the base film is, the better. A base film that is too hard will affect the effect of the second repair layer, and the preparation process of the present invention can produce a TPU film material of appropriate hardness. Since the base film material of the present invention is still TPU, it has high transparency, good tensile properties and impact resistance, and a second repair self-repair functional layer can still be made on the surface of the TPU film material, which is suitable for windshield and window stickers, has good adhesion, excellent explosion-proof effect, and can withstand long-term scraping by wipers without scratches.
[0032] (3) The explosion-proof film for car windows of the present invention still uses a base film made of TPU material, but the liquid TPU resin is used to adjust the formula of the TPU resin and improve the hardness of the TPU finished base film, so that it can be easily pasted on the car window, has a high hardness, is not easy to deform, and is resistant to scratches by wipers, but is not too hard to affect the effect of the second repair layer, thereby solving many defects of existing car window film materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a schematic diagram of the structure of the TPU film supported by non-silicone release films on both sides prepared in Example 1 of the present invention.
[0034] Figure 2 This is a schematic diagram of the structure of the TPU film with a second repair layer and a protective film prepared in Example 1 of the present invention.
[0035] Figure 3 This is a schematic diagram of the structure of the explosion-proof film for vehicle windows prepared in Example 1 of the present invention.
[0036] The numbers in the figure represent: 1. Non-silicone release film; 2. TPU film; 3. Second repair layer; 4. Protective film; 5. Release film; 6. Installation adhesive layer. DETAILED DESCRIPTION
[0037] The present invention is further described below in conjunction with the accompanying drawings and specific preferred embodiments, but the protection scope of the present invention is not limited thereby.
[0038] In the following examples of the present invention, unless otherwise specified, the materials and instruments used are commercially available, the equipment used is conventional equipment, and the data obtained are the average values of more than three repeated experiments.
[0039] Example 1
[0040] A method for preparing an explosion-proof film for a vehicle window according to the present invention comprises the following steps:
[0041] S1. The polyurethane coating liquid and the hexamethylene diisocyanate trimer curing agent are mixed evenly, and then the acetylacetonate-based organic tin catalyst, glycidyl ester, benzotriazole UV absorber, hindered amine type UV stabilizer and N, N-dimethylacetamide are added, and the mixture is mixed evenly and vacuum defoamed to prepare a pre-coating liquid, and the viscosity of the pre-coating liquid is 2950 mpa·s.
[0042] In this embodiment, the mass ratio of the polyurethane coating liquid to hexamethylene diisocyanate trimer curing agent, acetylacetonate-based organic tin catalyst, glycidyl ester, benzotriazole UV absorber, hindered amine type UV stabilizer, and N,N-dimethylacetamide is 100:2:2:1.5:0.5:0.3:10.
[0043] In this embodiment, the polyurethane coating liquid has a solid content of 38.2 wt%, a viscosity of 8200 mPa·s, a number average molecular weight of 42000 g / mol, and based on a solid content of 100 wt%, a hydroxyl value of the polyurethane coating liquid is 85 mgKOH / g, and an acid value of the polyurethane coating liquid is 12 mgKOH / g;
[0044] Polyurethane coating can be obtained by reacting polycarbonate polyol with isophorone diisocyanate (IPDI).
[0045] In this embodiment, the solid content of the hexamethylene diisocyanate trimer curing agent is 86wt%, the solid content of the acetylacetonate-based organotin catalyst is 2wt%, the solid content of the glycidyl ester is 10wt%, the solid content of the benzotriazole type UV absorber is 100wt%, and the solid content of the hindered amine type UV stabilizer is 100wt%. The hexamethylene diisocyanate trimer curing agent is manufactured by Covestro AG and has a brand name of N3300.
[0046] S2, the above-mentioned pre-coating liquid is evenly coated on the non-silicone release film 1 using a slit extrusion precision metering coater, and the coating amount of the pre-coating liquid is 168g / m 2 The coating thickness is 150um, and the coating line speed is set to 4m / min. After passing through a 120℃, 28m long oven and curing for 7min, the other side of the non-silicon release film 1 is compounded, rolled up, and aged at high temperature of 50℃ for 3 days to obtain a TPU film 2 supported by two non-silicon release films 1. Figure 1 shown.
[0047] S3. Mix hydroxy acrylate resin, isocyanate curing agent and ethyl acetate in a mass ratio of 100:30:25 to obtain a second repair coating with a solid content of 33.9wt% (theoretical calculated value). The viscosity of the second repair coating is 35mpa·s. Remove one of the non-silicone release films 1 on the TPU film 2 supported by the two non-silicone release films 1. Use a 110-mesh micro-concave diagonal roller to evenly apply the second repair coating on the TPU film 2 with one non-silicone release film 1 torn off. The coating amount of the second repair coating is 11.2g / m 2 The coating thickness is 10um, the coating line speed is set to 14m / min, and after drying and curing in an oven at 100℃ and 28m long for 2min, a second repair layer 3 is obtained. The low-dyne surface of the PET protective film is compounded on the second repair layer 3, such as Figure 2 shown.
[0048] The solid content of the hydroxy acrylic resin is 30 wt %; based on the solid content of 100 wt %, the hydroxy value of the hydroxy acrylic resin is 192 mgKOH / g; the isocyanate curing agent is hexamethylene diisocyanate biuret curing agent, and the solid content of the hexamethylene diisocyanate biuret curing agent is 75 wt %. The manufacturer of the hydroxy acrylic resin is Ningbo Funa New Material Technology Co., Ltd., with the brand name FNRG-0352S; the manufacturer of the hexamethylene diisocyanate biuret curing agent is Covestro AG, with the brand name N75.
[0049] S4, the installation glue and ethyl acetate are mixed in a mass ratio of 100:25 to obtain an installation glue coating liquid, the viscosity of the installation glue coating liquid is 1100mpa·s, and the installation glue coating liquid is coated on the release film 5 using a slit extrusion precision metering coating machine, and the coating amount of the installation glue coating liquid is 16.8g / m 2 The coating dry thickness is 15um, the coating line speed is set to 20m / min, and after being dried and cured in an oven at 120℃ and 28m long for 1.4min, the installation adhesive layer 6 is obtained. The other side of the non-silicone release film 1 on the TPU film 2 with the second repair layer 3 and the protective film 4 is torn off, and the installation adhesive layer 6 on the release film 5 is laminated, and then matured at 50℃ for 3 days to obtain the explosion-proof film for the car window. Figure 3 As shown in the figure, the installation glue is Bostik 951059.
[0050] The TPU base film prepared in step S2 was tested according to ASTM D2240, and the hardness was shore D42. The TPU base film prepared in step S2 was tested according to ASTM D882, and the tensile strength was 54 MPa. Simulating the customer's wiper scratching requirements, the window explosion-proof film prepared in step S4 was subjected to a 1 kg pressure and a dust-free cloth dipped in water and wiped back and forth 10,000 times. There were no scratches on the surface of the window explosion-proof film, and the base film had no orange peel and no deformation, which met the design goals.
[0051] Example 2
[0052] A method for preparing an explosion-proof film for a vehicle window according to the present invention comprises the following steps:
[0053] S1. The polyurethane coating liquid and the hexamethylene diisocyanate trimer curing agent are mixed evenly, and then the acetylacetonate-based organic tin catalyst, glycidyl ester, benzotriazole UV absorber, hindered amine type UV stabilizer and N, N-dimethylacetamide are added, and the mixture is mixed evenly and vacuum defoamed to prepare a pre-coating liquid, and the viscosity of the pre-coating liquid is 2680 mpa·s.
[0054] In this embodiment, the mass ratio of the polyurethane coating liquid to hexamethylene diisocyanate trimer curing agent, acetylacetonate-based organic tin catalyst, glycidyl ester, benzotriazole UV absorber, hindered amine type UV stabilizer, and N,N-dimethylacetamide is 100:2:2:1.5:0.5:0.3:10.
[0055] In this embodiment, the polyurethane coating liquid has a solid content of 37.9wt%, a viscosity of 7920mPa·s, a number average molecular weight of 38000g / mol, and a solid content of 100wt%. The hydroxyl value of the polyurethane coating liquid is 83mgKOH / g, and the acid value of the polyurethane coating liquid is 13mgKOH / g. The polyurethane coating liquid can be obtained by reacting polycarbonate polyol with isophorone diisocyanate (IPDI).
[0056] In this embodiment, the hexamethylene diisocyanate trimer curing agent does not contain a benzene ring, and will not turn yellow after aging. At the same time, the curing agent is hard and has a large crosslinking density, so that the hardness of the finished product is also high. Its solid content is 86wt%; the solid content of the acetylacetonate-based organic tin catalyst is 2wt%; the solid content of glycidyl ester is 10wt%; the solid content of the benzotriazole type ultraviolet absorber is 100wt%; the solid content of the hindered amine type ultraviolet stabilizer is 100wt%. The hexamethylene diisocyanate trimer curing agent is manufactured by Covestro AG and has a brand name of N3300.
[0057] S2, the above-mentioned pre-coating liquid is evenly coated on the non-silicone release film 1 using a slit extrusion precision metering coater, and the coating amount of the pre-coating liquid is 224g / m 2 The coating dry thickness is 200um, the coating line speed is set to 3m / min, and after passing through a 130℃, 28m long oven and curing for 9.3min, the other side of the non-silicone release film 1 is compounded, rolled up, and aged at a high temperature of 50℃ for 3 days to obtain a TPU film 2 supported by two sides of the non-silicone release film 1.
[0058] S3. Mix hydroxy acrylate resin, isocyanate curing agent and ethyl acetate in a mass ratio of 100:30:25 to obtain a second repair coating with a solid content of 33.9wt% (theoretical calculated value). The viscosity of the second repair coating is 42mpa·s. Remove one of the non-silicone release films 1 on the TPU film 2 supported by the two non-silicone release films 1. Use a micro-concave diagonal roller with an 80-mesh size to evenly apply the second repair coating on the TPU film 2 with one non-silicone release film 1 torn off. The coating amount of the second repair coating is 16.8g / m 2 The coating dry thickness is 15um, the coating line speed is set to 10m / min, and after being dried and cured in an oven at 110℃ and 28m long for 2.8min, a second repair layer 3 is obtained, and the low-dyne surface of the PET protective film is compounded on the second repair layer 3.
[0059] The solid content of the hydroxy acrylic resin is 30 wt %; based on the solid content of 100 wt %, the hydroxy value of the hydroxy acrylic resin is 192 mgKOH / g; the isocyanate curing agent is hexamethylene diisocyanate biuret curing agent, and the solid content of the hexamethylene diisocyanate biuret curing agent is 75 wt %. The manufacturer of the hydroxy acrylic resin is Ningbo Funa New Material Technology Co., Ltd., with the brand name FNRG-0352S, and the manufacturer of the hexamethylene diisocyanate biuret curing agent is Covestro AG, with the brand name N75.
[0060] S4, the installation glue and ethyl acetate are mixed in a mass ratio of 100:25 to obtain an installation glue coating liquid, the viscosity of the installation glue coating liquid is 1260mpa·s, and the installation glue coating liquid is coated on the release film 5 using a slit extrusion precision metering coating machine, and the coating amount of the installation glue coating liquid is 16.8g / m 2 The coating thickness is 15um, the coating line speed is set to 20m / min, and the installation adhesive layer 6 is obtained after being dried and cured in an oven at 120℃ and 28m long for 1.4min. The other side of the non-silicon release film 1 on the TPU film 2 with the second repair layer 3 and the protective film 4 is torn off, and the installation adhesive layer 6 on the release film 5 is laminated, and then matured at 50℃ for 3 days to obtain the explosion-proof film for the car window. Among them, the installation adhesive is Bostik 951059.
[0061] The TPU base film prepared in step S2 was tested according to ASTM D2240, and the hardness was shore D44. The TPU base film prepared in step (2) was tested according to ASTM D882, and the tensile strength was 58 MPa. Simulating the customer's wiper scratching requirements, the windshield shield prepared in step (4) was subjected to a 1 kg pressure and a dust-free cloth dipped in water to wipe back and forth 10,000 times. There were no scratches on the surface of the windshield shield, and the base film had no orange peel or deformation, all of which met the design goals.
[0062] Example 3
[0063] A method for preparing an explosion-proof film for a vehicle window according to the present invention comprises the following steps:
[0064] S1. The polyurethane coating liquid and the hexamethylene diisocyanate trimer curing agent are mixed evenly, and then the acetylacetonate-based organic tin catalyst, glycidyl ester, benzotriazole UV absorber, hindered amine type UV stabilizer and N, N-dimethylacetamide are added, and the mixture is mixed evenly and vacuum defoamed to prepare a pre-coating liquid, and the viscosity of the pre-coating liquid is 2630 mpa·s.
[0065] In this embodiment, the mass ratio of the polyurethane coating liquid to hexamethylene diisocyanate trimer curing agent, acetylacetonate-based organic tin catalyst, glycidyl ester, benzotriazole UV absorber, hindered amine type UV stabilizer, and N,N-dimethylacetamide is 100:2.5:2:1.5:0.5:0.3:10.
[0066] In this embodiment, the polyurethane coating liquid has a solid content of 38.3 wt%, a viscosity of 9260 mPa·s, a number average molecular weight of 45000 g / mol, and a solid content of 100 wt%. The hydroxyl value of the polyurethane coating liquid is 87 mgKOH / g, and the acid value of the polyurethane coating liquid is 14 mgKOH / g. The polyurethane coating liquid can be obtained by reacting polycarbonate polyol with isophorone diisocyanate (IPDI).
[0067] In this embodiment, the solid content of the hexamethylene diisocyanate trimer curing agent is 86wt%, the solid content of the acetylacetonate-based organotin catalyst is 2wt%, the solid content of the glycidyl ester is 10wt%, the solid content of the benzotriazole type UV absorber is 100wt%, and the solid content of the hindered amine type UV stabilizer is 100wt%. The hexamethylene diisocyanate trimer curing agent is manufactured by Covestro AG and has a brand name of N3300.
[0068] (2) The above-mentioned pre-coating liquid is evenly coated on the non-silicone release film 1 using a slit extrusion precision metering coater. The coating amount of the pre-coating liquid is 168 g / m 2 The coating dry thickness is 150um, the coating line speed is set to 4m / min, and after passing through a 120℃, 28m long oven and curing for 7min, the other side of the non-silicone release film 1 is compounded, rolled up, and aged at high temperature of 50℃ for 3 days to obtain a TPU film 2 supported by two sides of non-silicone release film 1.
[0069] (3) The hydroxy acrylate resin, isocyanate curing agent and ethyl acetate were mixed in a mass ratio of 100:30:25 to obtain a second repair coating liquid with a solid content of 33.9 wt% (theoretical calculated value). The viscosity of the second repair coating liquid was 38 mPa·s. One side of the non-silicone release film 1 on the TPU film 2 supported by the two non-silicone release films 1 was torn off. A 110-mesh micro-concave diagonal roller was used to evenly apply the second repair coating liquid on the TPU film 2 from which one non-silicone release film 1 was torn off. The coating amount of the second repair coating liquid was 11.2 g / m 2 The coating dry thickness is 10um, the coating line speed is set to 15m / min, and after being dried and cured in an oven at 100℃ and 28m long for 1.9min, a second repair layer 3 is obtained, and the low-dyne surface of the PET protective film is compounded on the second repair layer 3.
[0070] The solid content of the hydroxy acrylic resin is 30 wt %; based on the solid content of 100 wt %, the hydroxy value of the hydroxy acrylic resin is 192 mgKOH / g; the isocyanate curing agent is hexamethylene diisocyanate biuret curing agent, and the solid content of the hexamethylene diisocyanate biuret curing agent is 75 wt %. The manufacturer of the hydroxy acrylic resin is Ningbo Funa New Material Technology Co., Ltd., with the brand name FNRG-0352S; the manufacturer of the hexamethylene diisocyanate biuret curing agent is Covestro AG, with the brand name N75.
[0071] S4, the installation glue and ethyl acetate are mixed in a mass ratio of 100:25 to obtain an installation glue coating liquid, the viscosity of the installation glue coating liquid is 1130mpa·s, and the installation glue coating liquid is coated on the release film 5 using a slit extrusion precision metering coating machine, and the coating amount of the installation glue coating liquid is 16.8g / m 2The coating thickness is 15um, the coating line speed is set to 20m / min, and the installation adhesive layer 6 is obtained after being dried and cured in an oven at 120℃ and 28m long for 1.4min. The other side of the non-silicon release film 1 on the TPU film 2 with the second repair layer 3 and the protective film 4 is torn off, and the installation adhesive layer 6 on the release film 5 is laminated, and then matured at 50℃ for 3 days to obtain the explosion-proof film for the car window. Among them, the installation adhesive is Bostik 951059.
[0072] The TPU base film prepared in step S2 was tested according to ASTM D2240, and the hardness was shore D48. The TPU base film prepared in step S2 was tested according to ASTM D882, and the tensile strength was 62 MPa. Simulating the customer's wiper scratching requirements, the windshield shield prepared in step S4 was subjected to a 1 kg pressure and a dust-free cloth dipped in water to wipe back and forth 10,000 times. There were no scratches on the surface of the windshield shield, and the base film had no orange peel or deformation, all of which met the design goals.
[0073] Example 4
[0074] A method for preparing an explosion-proof film for a vehicle window according to the present invention comprises the following steps:
[0075] S1. The polyurethane coating liquid and the hexamethylene diisocyanate trimer curing agent are mixed evenly, and then the acetylacetonate-based organic tin catalyst, glycidyl ester, benzotriazole UV absorber, hindered amine type UV stabilizer and N, N-dimethylacetamide are added, and the mixture is mixed evenly and vacuum defoamed to prepare a pre-coating liquid, and the viscosity of the pre-coating liquid is 2520 mpa·s.
[0076] In this embodiment, the mass ratio of the polyurethane coating liquid to hexamethylene diisocyanate trimer curing agent, acetylacetonate-based organic tin catalyst, glycidyl ester, benzotriazole UV absorber, hindered amine type UV stabilizer, and N,N-dimethylacetamide is 100:2.5:2:1.5:0.5:0.3:10.
[0077] In this embodiment, the polyurethane coating liquid has a solid content of 37.8 wt%, a viscosity of 8170 mPa·s, a number average molecular weight of 34000 g / mol, and a solid content of 100 wt%. The hydroxyl value of the polyurethane coating liquid is 80 mgKOH / g, and the acid value of the polyurethane coating liquid is 12 mgKOH / g. The polyurethane coating liquid can be obtained by reacting polycarbonate polyol with isophorone diisocyanate (IPDI).
[0078] In this embodiment, the solid content of the hexamethylene diisocyanate trimer curing agent is 86wt%, the solid content of the acetylacetonate-based organotin catalyst is 2wt%, the solid content of the glycidyl ester is 10wt%, the solid content of the benzotriazole type UV absorber is 100wt%, and the solid content of the hindered amine type UV stabilizer is 100wt%. The hexamethylene diisocyanate trimer curing agent is manufactured by Covestro AG and has a brand name of N3300.
[0079] S2, the above-mentioned pre-coating liquid is evenly coated on the non-silicone release film 1 using a slit extrusion precision metering coater, and the coating amount of the pre-coating liquid is 224g / m 2 The coating dry thickness is 200um, the coating line speed is set to 3m / min, and after passing through a 130℃, 28m long oven and curing for 9.3min, the other side of the non-silicone release film 1 is compounded, rolled up, and aged at a high temperature of 50℃ for 3 days to obtain a TPU film 2 supported by two sides of the non-silicone release film 1.
[0080] S3. Mix hydroxy acrylate resin, isocyanate curing agent and ethyl acetate in a mass ratio of 100:30:25 to obtain a second repair coating with a solid content of 33.9wt% (theoretical calculated value). The viscosity of the second repair coating is 34mpa·s. Remove one of the non-silicone release films 1 on the TPU film 2 supported by the two non-silicone release films 1. Use a micro-concave diagonal roller with an 80-mesh size to evenly apply the second repair coating on the TPU film 2 with one non-silicone release film 1 torn off. The coating amount of the second repair coating is 16.8g / m 2 The coating dry thickness is 15um, the coating line speed is set to 10m / min, and after being dried and cured in an oven at 110℃ and 28m long for 2.8min, a second repair layer 3 is obtained, and the low-dyne surface of the PET protective film is compounded on the second repair layer 3.
[0081] The solid content of the hydroxy acrylic resin is 30 wt %; based on the solid content of 100 wt %, the hydroxy value of the hydroxy acrylic resin is 192 mgKOH / g; the isocyanate curing agent is hexamethylene diisocyanate biuret curing agent, and the solid content of the hexamethylene diisocyanate biuret curing agent is 75 wt %. The manufacturer of the hydroxy acrylic resin is Ningbo Funa New Material Technology Co., Ltd., with the brand name FNRG-0352S; the manufacturer of the hexamethylene diisocyanate biuret curing agent is Covestro AG, with the brand name N75.
[0082] S4, the installation glue and ethyl acetate are mixed in a mass ratio of 100:25 to obtain an installation glue coating liquid, the viscosity of the installation glue coating liquid is 1210mpa·s, and the installation glue coating liquid is coated on the release film 5 using a slit extrusion precision metering coating machine, and the coating amount of the installation glue coating liquid is 16.8g / m 2The coating thickness is 15um, the coating line speed is set to 20m / min, and the installation adhesive layer 6 is obtained after being dried and cured in an oven at 120℃ and 28m long for 1.4min. The other side of the non-silicon release film 1 on the TPU film 2 with the second repair layer 3 and the protective film 4 is torn off, and the installation adhesive layer 6 on the release film 5 is laminated, and then matured at 50℃ for 3 days to obtain the explosion-proof film for the car window. Among them, the installation adhesive is Bostik 951059.
[0083] The TPU base film prepared in step S2 was tested according to ASTM D2240, and the hardness was shore D48. The TPU base film prepared in step S2 was tested according to ASTM D882, and the tensile strength was 63 MPa. Simulating the customer's wiper scratching requirements, the windshield shield prepared in step S4 was subjected to a 1 kg pressure and a dust-free cloth dipped in water to wipe back and forth 10,000 times. There were no scratches on the surface of the windshield shield, and the base film had no orange peel or deformation, all of which met the design goals.
[0084] Comparative Example 1
[0085] A method for preparing a vehicle window film, wherein the experimental steps are substantially the same as those of Example 1, except that in this comparative example, a commercially available TPU base film prepared by a conventional casting method is directly used to carry out the processes of step S3 and step S4 to prepare the vehicle window film.
[0086] The commercially available TPU base film prepared by conventional casting method has a thickness of 150um and is provided with a double-sided non-silicone release film. The manufacturer of the TPU base film is Zhejiang Newcastle New Materials Technology Co., Ltd. and the brand number is NCS290.
[0087] The commercially available TPU base film prepared by the conventional casting method was tested with reference to the testing method of Example 1, and the hardness was shore A92 and the tensile strength was 38 MPa, which were significantly lower than the TPU film 2 of the present invention. Simulating the customer's wiper scratching requirements, the window film prepared in this comparative example was subjected to a 1 kg pressure and a dust-free cloth dipped in water and wiped back and forth 10,000 times. There were no scratches on the surface of the window film, but the base film showed obvious orange peel and deformation, which could not meet the design goals.
[0088] Comparative Example 2
[0089] A method for preparing a vehicle window film, the experimental steps are basically the same as those of Example 2, the main difference being that in this comparative example, a commercially available TPU base film prepared by a conventional casting method is directly used to carry out the processes of step S3 and step S4 to prepare the vehicle window film.
[0090] The commercially available TPU base film prepared by conventional casting method has a thickness of 150um and is provided with a double-sided non-silicone release film. The manufacturer of the TPU base film is Zhejiang Newcastle New Materials Technology Co., Ltd. and the brand number is NCS290.
[0091] The commercially available TPU base film prepared by the conventional casting method was tested with reference to the testing method of Example 1, and the hardness was shore A92 and the tensile strength was 40 MPa, which were significantly lower than the TPU film 2 of the present invention. Simulating the customer's wiper scratching requirements, the window film prepared in this comparative example was subjected to a 1 kg pressure and a dust-free cloth dipped in water and wiped back and forth 10,000 times. There were no scratches on the surface of the window film, but the base film showed obvious orange peel and deformation, which could not meet the design goals.
[0092] Comparative Example 3
[0093] A method for preparing a vehicle window film, wherein the experimental steps are substantially the same as those of Example 1, the main difference being that, in this comparative example, no glycidyl ester is added.
[0094] The TPU base film prepared in step S2 was tested with reference to the testing method of Example 1, and the hardness was shore D40 and the tensile strength was 48 MPa, which were slightly lower than the TPU film 2 of the present invention, and the tensile strength was lower than the TPU film 2 of the present invention. Simulating the customer's wiper scratching requirements, the window explosion-proof film prepared in step S4 was subjected to a 1 kg pressure and a dust-free cloth dipped in water and wiped back and forth 10,000 times. There were no scratches on the surface of the window explosion-proof film, and the base film had no orange peel and no deformation. The initial performance met the design goals.
[0095] Further durability tests were conducted. The film materials prepared in Example 1 and Comparative Example 3 were respectively pasted on glass plates, and test strips with release films were cut (for tensile strength testing) and placed in an aging box at 85°C and 85%RH. After 28 days, the two film materials were taken out and the tensile strength was tested. The explosion-proof film for the car window prepared in Example 1 had a tensile strength of 50Mpa, with basically no attenuation, and the film material could be completely torn off from the glass plate; the explosion-proof film for the car window prepared in Comparative Example 3 had a tensile strength of 8Mpa, with severe attenuation, and the film material could not be torn off from the glass plate, and hydrolysis occurred. The main reason is that the monoepoxy functional carboxyl remover of the glycidyl ester type was not added in Comparative Example 3, and the prepared base film had a high carboxyl content. Under high temperature and high humidity conditions, the carboxyl group would catalyze the hydrolysis of the ester group on the main chain, causing the explosion-proof film for the car window to drop rapidly in tensile strength under 85°C and 85%RH humidity aging conditions, and could not be torn off from the glass. In actual use, after a few years, the explosion-proof film on the car window needs to be removed and replaced with a new one. However, it may be impossible to remove and clean it, which leads to troublesome replacement, increased replacement costs, and shorter replacement time.
[0096] Although the present invention is disclosed as above with preferred embodiments, it is not intended to limit the present invention. Any technician familiar with the art can use the above disclosed methods and technical contents to make many possible changes and modifications to the technical solutions of the present invention without departing from the spirit and technical solutions of the present invention, or modify them into equivalent embodiments of equivalent changes. Therefore, any simple modification, equivalent replacement, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solutions of the present invention still fall within the scope of protection of the technical solutions of the present invention.
Claims
1. A method for preparing an explosion-proof film for a vehicle window, characterized in that: The following steps are involved: S1, dissolving a polyurethane coating liquid, an isocyanate curing agent, a metal chelate catalyst, a carboxyl remover, an ultraviolet absorber and an ultraviolet stabilizer in an organic solvent, mixing, and vacuum defoaming to obtain a pre-coating liquid; S2, coating the pre-coating liquid obtained in step S1 on the non-silicon release film (1), drying and curing, and then compounding the non-silicon release film (1) on the other side, rolling up, and ripening to obtain a TPU film (2) supported by the non-silicon release films (1) on both sides; S3, dissolving a hydroxy acrylate resin and an isocyanate curing agent in an organic solvent, mixing, and obtaining a second-repair coating liquid, tearing off one of the non-silicon release films (1) on the TPU film (2) supported by the two non-silicon release films (1) obtained in step S2, coating the second-repair coating liquid on the TPU film (2) from which one non-silicon release film (1) has been torn off, drying and curing to obtain a second-repair layer (3), and compounding a protective film (4) on the second-repair layer (3); S4, the installation glue is mixed with an organic solvent to obtain an installation glue coating liquid, which is applied on the release film (5), and after drying and curing, an installation glue layer (6) is obtained. The other side of the non-silicon release film (1) on the TPU film (2) having the second repair layer (3) and the protective film (4) in step S3 is torn off, and the installation glue layer (6) on the release film (5) is laminated and cured to obtain an explosion-proof film for the vehicle window.
2. The method for preparing an explosion-proof film for vehicle windows according to claim 1, characterized in that: In step S1, the mass ratio of the polyurethane coating liquid to the isocyanate curing agent, the metal chelate catalyst, the carboxyl remover, the ultraviolet absorber, the ultraviolet stabilizer and the organic solvent is 100:1.5-2.5:1.5-2.5:1.0-2.0:0.4-0.6:0.2-0.4:8-15.
3. The method for preparing an explosion-proof film for vehicle windows according to claim 2, characterized in that: In step S1, the polyurethane coating liquid has a solid content of 35wt% to 40wt%, a viscosity of 7000mpa·s to 10000mpa·s, and a number average molecular weight of 30000g / mol to 50000g / mol; based on a solid content of 100wt%, a hydroxyl value of the polyurethane coating liquid is 60mgKOH / g to 120mgKOH / g, and an acid value of the polyurethane coating liquid is 5mgKOH / g to 15mgKOH / g; In step S1 and step S3, the isocyanate curing agent is one or both of hexamethylene diisocyanate biuret curing agent and hexamethylene diisocyanate trimer curing agent; In step S1, the metal chelate catalyst is one or more of acetylacetonato organic tin, acetylacetonato organic bismuth, acetylacetonato organic zinc and acetylacetonato organic aluminum; In step S1, the carboxyl group removing agent is one or more of glycidyl ester, glycidyl ether, glycidyl amine and carbodiimide; In step S1, the ultraviolet absorber is one or more of a benzophenone ultraviolet absorber, a benzotriazole ultraviolet absorber and a triazine ultraviolet absorber.
4. The method for preparing an explosion-proof film for vehicle windows according to claim 3, characterized in that: In step S1, the solid content of the polyurethane coating liquid is 37wt% to 39wt%; based on the solid content of 100wt%, the hydroxyl value of the polyurethane coating liquid is 79mgKOH / g to 88mgKOH / g, and the acid value of the polyurethane coating liquid is 10mgKOH / g to 15mgKOH / g; the polyurethane coating liquid is prepared by polycarbonate polyol and isophorone diisocyanate; In step S1 and step S3, the isocyanate curing agent is a hexamethylene diisocyanate trimer curing agent, and the solid content of the hexamethylene diisocyanate trimer curing agent is 80wt% to 90wt%; In step S1, the metal chelate catalyst is an acetylacetonate-based organotin catalyst, and the solid content of the acetylacetonate-based organotin catalyst is 2 wt% to 2.5 wt%; In step S1, the carboxyl removing agent is glycidyl ester, and the solid content of the glycidyl ester is 9wt% to 11wt%; In step S1, the ultraviolet absorber is a benzotriazole ultraviolet absorber, and the solid content of the benzotriazole ultraviolet absorber is 98wt% to 100wt%; In step S1, the UV stabilizer is a hindered amine type UV stabilizer, and the solid content of the hindered amine type UV stabilizer is 98wt% to 100wt%.
5. The method for preparing the explosion-proof film for vehicle windows according to claim 1, characterized in that: In step S3, the mass ratio of the hydroxy acrylate resin to the isocyanate curing agent and the organic solvent is 100:28-32:20-40; The solid content of the hydroxy acrylic resin is 30 wt % to 40 wt %, and the hydroxy value of the hydroxy acrylic resin is 190 mgKOH / g to 200 mgKOH / g; the solid content of the isocyanate curing agent is 73 wt % to 77 wt %.
6. The method for preparing the explosion-proof film for vehicle windows according to claim 1, characterized in that: The organic solvent in step S1 is one or more of ethyl acetate, butyl acetate, acetone, butanone, N,N-dimethylformamide, N,N-diethylformamide, N,N-dimethylacetamide and N,N-diethylacetamide; In step S3 and step S4, the organic solvent is one or more of ethyl acetate, butyl acetate, acetone and butanone.
7. The method for preparing an explosion-proof film for vehicle windows according to claim 1, characterized in that: In step S1, the viscosity of the pre-coating liquid is 2000mpa·s to 3500mpa·s. In step S2, the coating amount of the pre-coating liquid is 168g / m 2 ~224g / m 2 ; In step S3, the viscosity of the second repair coating is 10mpa·s to 100mpa·s, and the coating amount of the second repair coating is 11.2g / m 2 ~16.8g / m 2 ; In step S4, the viscosity of the installation glue coating liquid is 500mpa·s to 2000mpa·s, and the coating amount of the installation glue coating liquid is 16.8g / m 2 ~22.4g / m 2 .
8. The method for preparing an explosion-proof film for vehicle windows according to any one of claims 1 to 7, characterized in that: In step S2, the coating is carried out by a precision coating machine, the running speed of the pre-coating liquid on the precision coating machine is 3m / min to 5m / min, the drying temperature is 100°C to 130°C, and the curing time is 6min to 10min; the aging temperature is 45°C to 55°C, and the aging time is 3 days to 5 days; In step S3, the coating is performed by a precision coating machine, the running speed of the second repair coating liquid on the precision coating machine is 10m / min to 15m / min, the drying temperature is 100°C to 110°C, and the curing time is 2min to 3min; In step S4, the coating is carried out by a precision coating machine, the running speed of the installation glue coating on the precision coating machine is 15m / min~20m / min, the drying temperature is 120℃~130℃, and the curing time is 1min~2min; the aging temperature is 45℃~55℃, and the aging time is 2 days~3 days; the installation glue adopts Bostik 951059 series.
9. An explosion-proof film for vehicle windows prepared by the preparation method according to any one of claims 1 to 8, characterized in that: It comprises a protective film (4), a second repair layer (3), a TPU film (2), a mounting adhesive layer (6), and a release film (5) which are laminated in sequence. The TPU film has a visible light transmittance of ≥88%, a Shore hardness of D40-D50, and a tensile strength of ≥50Mpa.
10. The explosion-proof film for vehicle windows according to claim 9, characterized in that: The thickness of the instant repair layer (3) is 10 μm to 15 μm; the thickness of the TPU film (2) is 150 μm to 200 μm; the thickness of the installation adhesive layer (6) is 15 μm to 20 μm, and the adhesion of the installation adhesive layer (6) to glass is ≥1200 g / 25 mm.
Citation Information
Patent Citations
Externally-pasted heat insulation window film and preparation method thereof
CN117801717A